2016
DOI: 10.4292/wjgpt.v7.i4.469
|View full text |Cite
|
Sign up to set email alerts
|

Bilirubin in coronary artery disease: Cytotoxic or protective?

Abstract: Bilirubin has traditionally been considered a cytotoxic waste product. However, recent studies have shown bilirubin to have anti-oxidant, anti-inflammatory, vasodilatory, anti-apoptotic and anti-proliferative functions. These properties potentially confer bilirubin a new role of protection especially in coronary artery disease (CAD), which is a low grade inflammatory process exacerbated by oxidative stress. In fact, recent literature reports an inverse relationship between serum concentration of bilirubin and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 49 publications
0
20
0
3
Order By: Relevance
“…However, our results remain significant when smoking status is adjusted for the analysis. Several prospective studies did not found protective effect of bilirubin on CVD [ 21 ]. However, these studies were limited by its small sample size or patients with high risk profile for CVD.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results remain significant when smoking status is adjusted for the analysis. Several prospective studies did not found protective effect of bilirubin on CVD [ 21 ]. However, these studies were limited by its small sample size or patients with high risk profile for CVD.…”
Section: Discussionmentioning
confidence: 99%
“…Low bilirubin levels can be indicative of decreased heme oxygenase activity (a powerful antioxidant) or could be indicative of high oxidative stress in patients leading to consumption of the natural antioxidants including bilirubin. Hence, there is possibility that lower levels of bilirubin are perhaps not the causal factor for CVD but may indicate patients at an increased risk of developing CVD [ 21 ]. Moreover, further large scale long-term study will be required to confirm our results regarding inflammation and IR in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Ritonavir-boosted atazanavir (ATV/r) has been associated with a lower cardiovascular risk than ritonavir-boosted darunavir [9]. This could be related to the ability of ATV/r to increase bilirubin levels, because bilirubin has been related to cardio-protective anti-oxidant effects [10].…”
Section: Introductionmentioning
confidence: 99%
“…IDB is converted to DB in hepatic cells and excreted into bile acid. 1 Considered to be a waste product at first, bilirubin now has been known to have antioxidative, 2 anti-inflammatory, 3 and antithrombotic effects. 4 However, epidemiologic studies lack consistency.…”
mentioning
confidence: 99%